Harnessing the Prior Ideas: New Researchers' Challenges of Finding a Research Gap in Review of Literature - Sharma, Bal Krishna (Haimaprabha, 2025)
This article examines explores the problems that novice researchers encounter while conducting a review of literature. Anchored to this common problem, this article aims at assisting how beginner researchers can review the existing body of knowledge in their chosen field of research. It has been framed around three specific rhetorical moves: first, it identifies the problems that student researchers encounter; second, it shows how the problems can be addressed; and lastly, it draws a conclusion and suggests useful recommendations. So, beginning with the first move, the paper examines that students of research writing generally fail to trace the gap in the literature to articulate their stance. The article's second move emphasizes that the most effective way to identify gaps in the current body of literature is to develop a systematic and preplanned strategy. In its last part, the article concludes that writers new to research writing cannot produce a well-reasoned research study because they lack the skills to argue their case cogently. Informed by the views of prominent theorists on research and that of a review of literature, this article argues that novice researchers struggle to pinpoint gaps and inconsistencies in past literature and fail to integrate their research with the ongoing and past scholarship. On the basis of this argument, the paper recommends that novice researchers should seek feedback from the senior supervisors from related departments in the process of writing a literature review. To discuss this argument, the paper follows the qualitative research design prevalent in the Humanities and English Studies and draws relevant data from the secondary sources that examine how naïve researchers should conduct a review of literature to construct an argument in their research papers.